2017
DOI: 10.1002/ptr.5815
|View full text |Cite
|
Sign up to set email alerts
|

Resistance-modifying Activity in Vinblastine-resistant Human Breast Cancer Cells by Oligosaccharides Obtained from Mucilage of Chia Seeds (Salvia hispanica)

Abstract: The multidrug resistance (MDR) phenotype is considered as a major cause of the failure in cancer chemotherapy. The acquisition of MDR is usually mediated by the overexpression of drug efflux pumps of a P-glycoprotein. The development of compounds that mitigate the MDR phenotype by modulating the activity of these transport proteins is an important yet elusive target. Here, we screened the saponification and enzymatic degradation products from Salvia hispanica seed's mucilage to discover modulating compounds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…Antiproliferative effect of different parts of some Salvia species have been reported previously [14,15], while there was a few studies reported on Salvia seeds. Effects of four compounds obtained from mucilage of S. hispanica seeds were investigated against eight cancer lines [colon (HCT-15 and HCT-116), cervix (HeLa), breast (MCF7 and MDA-MB-231) carcinoma cell lines, MCF7/Vin+, MCF7/Vin, MCF7/Vin-cells, and Vero cells], and compounds were significantly inhibited the proliferation of HeLa, MCF7, and HepG2 cells with low toxicity in a normal cell model [35]. In the literature, cytotoxic effects on DU145 prostate cancer cell lines of dichloromethane and methanol extracts of S. pilifera were studied [15]; however, we didn't reach any available literature on antiproliferative effects of S. pilifera mericarps.…”
Section: Discussionmentioning
confidence: 99%
“…Antiproliferative effect of different parts of some Salvia species have been reported previously [14,15], while there was a few studies reported on Salvia seeds. Effects of four compounds obtained from mucilage of S. hispanica seeds were investigated against eight cancer lines [colon (HCT-15 and HCT-116), cervix (HeLa), breast (MCF7 and MDA-MB-231) carcinoma cell lines, MCF7/Vin+, MCF7/Vin, MCF7/Vin-cells, and Vero cells], and compounds were significantly inhibited the proliferation of HeLa, MCF7, and HepG2 cells with low toxicity in a normal cell model [35]. In the literature, cytotoxic effects on DU145 prostate cancer cell lines of dichloromethane and methanol extracts of S. pilifera were studied [15]; however, we didn't reach any available literature on antiproliferative effects of S. pilifera mericarps.…”
Section: Discussionmentioning
confidence: 99%
“…Given the previous claim of EPAʼs role in encouraging caspase activity, chia or similarly constituted seeds may have unpredicted antitumor potential; however, the limitation that chia did not make significant improvements compared to the safflower oil group must be emphasized. Additionally, a 2017 cytotoxicity study by Rosas-Ramirez et al [13] examined the effect of chia oligosaccharide mucilages in modifying the resistance and decreasing proliferation of cancerous cells, especially HeLa, MCF7, and HepG2 cells. The author of this study points out that the assurance that these mucilages do not attack noncancerous cells has yet to be achieved.…”
Section: Health Benefits Attributed To Chia Seeds and Oilmentioning
confidence: 99%
“…Asimismo, los resultados negativos contrastan con el estudio de Rosas-Ramirez et al donde se evaluaron los polisacáridos del mucílago de las semillas de Salvia hispanica para descubrir compuestos moduladores de la resistencia a quimioterapéuticos en células de cáncer de mama, obteniéndose una actividad moderada en potenciar en alrededor de cinco veces la respuesta al fármaco vinblastina en líneas celulares con multidrogo resistencia por sobre expresión de la P-glicoproteina. Por lo que, además de los antioxidantes, los polisacáridos de Salvia hispanica podrían tener un efecto significativo desde una perspectiva terapéutica [13] . Por lo tanto, la pobre actividad desmutagénica de las semillas de Salvia hispanica frente al daño producido por la azida de sodio probablemente se deba a la poca concentración evaluada.…”
Section: Discussionunclassified
“…Salvia hispanica L., es una planta herbácea de la familia de las lamiáceas, localmente conocida por sus usos medicinales, y con el nombre común de "chía", proveniente de los pueblos indígenas de las épocas precolombinas y aztecas. Sus semillas son ricas en ácidos grasos omega 3, 6 y 9, fibras y una gran cantidad de antioxidantes, por lo que recientemente se ha ampliado su uso para varios beneficios para la salud; por ejemplo, se han encontrado estudios previos donde se demuestra la actividad antitumoral de extractos de esta especie vegetal en adenocarcinoma de mama murina y como modificador de la resistencia a vinblastina en células cancerígenas de mama in vitro [11][12][13] .…”
Section: Introductionunclassified